Evaluation of the antimicrobial property of the lyophilized ethanolic peel extract of Citrus microcarpa Bunge (Fam. Rutaceae) - Alfonso, Jael Danielle Joelle P.
The calamansi fruit is known for its nutritive value and its importance to food industries in the production of acid beverages. Byproducts of most Citrus spp. In industries are processed in to animal feed and raw material used for the extraction of marketable products. However, the peels of citrus app. Largely contain valuable flavonoids which may posses health related properties. In this study, the lyophilized ethanolic extract of the rind of Citrus microcarpa Bunge (Fam. Rutaceae) was subjected to phytochemical screening and antimicrobialassay using disc diffusion method. The result of phytochemical screening indicate that the lyophilized ethanolic calamansi peel extract is acidic and contains substances which belong to the groups of tannins, glycosides, and reducing substances. Its antimicrobial activity against Pseudomonas aeruginosa. Escherichia coli, and Bacillus subtilis were observed in the antimicrobial assay. However, the extracts are not as effective as the Mupirocin (Bactroban) standard. Furthermore, it was noted that the solubility of the extract is essential in its antimicrobial activity against P. aeruginosa.